(untitled) (Italian Review of Legal History, 2024)
The precautionary principle has acquired a decisive place in national and international law. It is a principle of action that no longer aims to prevent a known risk with proven scientific certainty, but to take precautions against an unknown risk, the probability of which we cannot even assess, with immeasurable consequences. Initially a moral principle, it has become a legal principle by being enshrined in international, European, and national texts. Its initial scope of application, relating to the environment, has subsequently been extended to health and new technologies. This article traces a brief history of its birth and development from a legal-comparative perspective.